Caging Nb2O5 Nanowires in PECVD‐Derived Graphene Capsules toward Bendable Sodium‐Ion Hybrid Supercapacitors. Issue 26 (14th May 2018) - Wang, Xiangguo; Li, Qiucheng; Zhang, Li; Hu, Zhongli; Yu, Lianghao; Jiang, Tao; Lu, Chen; Yan, Chenglin; Sun, Jingyu; Liu, Zhongfan
Abstract: Sodium‐ion hybrid supercapacitors (Na‐HSCs) by virtue of synergizing the merits of batteries and supercapacitors have attracted considerable attention for high‐energy and high‐power energy‐storage applications. Orthorhombic Nb2 O5 ( T ‐Nb2 O5 ) has recently been recognized as a promising anode material for Na‐HSCs due to its typical pseudocapacitive feature, but it suffers from intrinsically low electrical conductivity. Reasonably high electrochemical performance of T ‐Nb2 O5 ‐based electrodes could merely be gained to date when sufficient carbon content was introduced. In addition, flexible Na‐HSC devices have scarcely been demonstrated by far. Herein, an in situ encapsulation strategy is devised to directly grow ultrathin graphene shells over T ‐Nb2 O5 nanowires (denoted as Gr‐Nb2 O5 composites) by plasma‐enhanced chemical vapor deposition, targeting a highly conductive anode material for Na‐HSCs. The few‐layered graphene capsules with ample topological defects would enable facile electron and Na + ion transport, guaranteeing rapid pseudocapacitive processes at the Nb2 O5 /electrolyte interface. The Na‐HSC full‐cell comprising a Gr‐Nb2 O5 anode and an activated carbon cathode delivers high energy/power densities (112.9 Wh kg −1 /80.1 W kg −1 and 62.2 Wh kg −1 /5330 W kg −1 ), outperforming those of recently reported Na‐HSC counterparts. Proof‐of‐concept Na‐HSC devices with favorable mechanical robustness manifest stable electrochemical performances under different bending conditions and after various bending–release cycles. Abstract : Graphene‐shell‐encapsulated orthorhombic Nb2 O5 nanowires prepared via plasma‐enhanced chemical vapor deposition are employed as electronic and ionic coconductive anodes for sodium‐ion hybrid supercapacitors (Na‐HSCs), realizing high energy/power densities (112.9 Wh kg −1 /80.1 W kg −1 and 62.2 Wh kg −1 /5330 W kg −1 ). Bendable Na‐HSC devices as a proof‐of‐concept demonstration manifest stable electrochemical performances under various deformation conditions and after bending–release cycles.